Putusan Mahkamah Konstitusi Dan Implikasinya Terhadap Pencari Keadilan - Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2008)
The verdict of the Constitutional Court, as the nature of a court decision, implies the rights that the justice seekers enjoy. It is unfortunate however, the appeal procedure for those who are not satisfied with such verdict is not issued yet, and this may produce the disadvantages for the purpose of affording justice. For such reason, the amendment on the Constitutional Court procedures, particularly in appeal procedures, is highly demanded.